O ser alcoolista: estudo compreensivo à luz da análise existencial - Silva Junior, Ivando Amancio da (2012)
The problem of alcoholism is evident in the effects of this drug, and cause social complications, consequences can produce organic, mint and spiritual. The problems arising from the misuse of alcohol can produce various effects easily observed in daily life. In order to understand the being alcoholic, seek theoretical support in Existential Analysis by being linked to the precepts phenomenological understanding and have a concern with the meaning of being. The test was performed in a Psychosocial Care Center Alcohol and other Drugs - CAPSad, located in the city of Fortaleza. Eight subjects participated in the study, meeting the criterion of saturation data. The production of empirical material occurred in the period September-October 2012, with interviews conducted, using a script containing questions relating to personal and sociodemographic aspects and a question: What is for you to be an alcoholic? A comprehensive analysis - phenomenological approach allowed the survival of favored individuals and the understanding of the phenomenon under study. The study was approved by the Ethics Committee of the Federal University of Ceará, as Opinion No. 04555112.2.0000.5054. Based on reading and seizure of talks were established thematic categories and 14 subcategories. The categories were defined, first, based on the trajectory of alcohol use and its impact on the lives of individuals, and is composed of nine subcategories: Initial contact with drugs; Sporadic other drugs concomitantly with alcohol, the search for fun and pleasure as encouraging the use of alcohol; Effects of alcohol use and abuse in the lives of individuals; Lack of sense of life caused by alcohol; Coping and Overcoming used by subjects: Search support network of healthcare services , Spirituality in support of the process of overcoming; Family support in difficult times; Personal difficulties experienced during treatment. Willpower as a coping strategy for withdrawal. The second category was defined with the meaning of being an alcoholic, composed of three subcategories: Being an alcoholic is death; Being an alcoholic is before a relationship of dependency; Being an alcoholic is to be sick. The survey favored the understanding of being an alcoholic, based on the precepts of Existential Analysis, allowing the search for the meaning of life through responsibility, freedom, ability to create, love, and transcendence that may contribute for better reflection of nursing practice developed in specialized services. One can grasp the idea that the individual alcoholic, even pervaded by existential conflicts and the various losses he had in his life, is a being who sought outputs and tried to stay alive, even in the face of adversity, as illustrated in their understanding phenomena and as being in the world. The meaning of being an alcoholic, seized the discourse of the study subjects is of endless possibilities, leading to understanding and experiential aspects of their life histories involving various feelings and repercussions for their relationship with themselves, with others and with the world around him. It is considered that the apprehension of the meaning that each subject gives the condition of being an alcoholic and enables the better understanding of their relationship with the drug, favoring the care process and even the attention the problems experienced.